A comparative molecular dynamics study on BACE1 and BACE2 flap flexibility. (2nd September 2016) - Kumalo, H. M.; Soliman, Mahmoud E.
Abstract: Beta-amyloid precursor protein cleavage enzyme1 (BACE1) and beta-amyloid precursor protein cleavage enzyme2 (BACE2), members of aspartyl protease family, are close homologs and have high similarity in their protein crystal structures. However, their enzymatic properties are different, which leads to different clinical outcomes. In this study, we performed sequence analysis and all-atom molecular dynamic (MD) simulations for both enzymes in their ligand-free states in order to compare their dynamical flap behaviors. This is to enhance our understanding of the relationship between sequence, structure and the dynamics of this protein family. Sequence analysis shows that in BACE1 and BACE2, most of the ligand-binding sites are conserved, indicative of their enzymatic property as aspartyl protease members. The other conserved residues are more or less unsystematically localized throughout the structure. Herein, we proposed and applied different combined parameters to define the asymmetric flap motion; the distance, d 1, between the flap tip and the flexible region; the dihedral angle, φ, to account for the twisting motion and the TriCα angle, θ 2 and θ 1 . All four combined parameters were found to appropriately define the observed "twisting" motion during the flaps different conformational states. Additional analysis of the parameters indicated that the flaps can exist in an ensemble of conformations, i.e. closed, semi-open and open conformations for both systems. However, the behavior of the flap tips during simulations is different between BACE1 and BACE2. The BACE1 active site cavity is more spacious as compared to that of BACE2. The analysis of 10S loop and 113S loop showed a similar trend to that of flaps, with the BACE1 loops being more flexible and less stable than those of BACE2. We believe that the results, methods and perspectives highlighted in this report would assist researchers in the discovery of BACE inhibitors as potential Alzheimer's disease therapies.